Peculiarities of Teaching Reading and Developing Reading Skills in a Foreign Language - Alimova Kamola Mirshahidovna (International Journal on Integrated Education, 2022)
The article deals with the issues based on teaching reading in a foreign language, considering some of the ways to develop reading skills. Reading is one of the receptive skills: the reader approaches the interpretation of texts with his source of knowledge and experience, which explains the unequal interpretation of the meaning of the same text by different readers. In the course of teaching to read, students try to exchange their thoughts about what they have read, learn the ways of asking questions. The teacher, in turn, acts as a kind of moderator between the students and the text.